The Influence of Phonomotor Treatment on Word Retrieval: Insights From Naming Errors. - Minkina, Irene; Silkes, JoAnn P.; Bislick, Lauren; Madden, Elizabeth Brookshire; Lai, Victoria; Pompon, Rebecca Hunting; Torrence, Janaki; Zimmerman, Reva M.; Kendall, Diane L. (Journal of Speech, Language & Hearing Research, 2019)
Purpose: An increasing number of anomia treatment studies have coupled traditional word retrieval accuracy outcome measures with more fine-grained analysis of word retrieval errors to allow for more comprehensive measurement of treatment-induced changes in word retrieval. The aim of this study was to examine changes in picture naming errors after phonomotor treatment. Method: Twenty-eight individuals with aphasia received 60 hr of phonomotor treatment, an intensive, phoneme-based therapy for anomia. Confrontation naming was assessed pretreatment, immediately posttreatment, and 3 months posttreatment for trained and untrained nouns. Responses were scored for accuracy and coded for error type, and error proportions of each error type (e.g., semantic, phonological, omission) were compared: pre- versus posttreatment and pretreatment versus 3 months posttreatment. Results: The group of treatment participants improved in whole-word naming accuracy on trained items and maintained their improvement. Treatment effects also generalized to untrained nouns at the maintenance testing phase. Additionally, participants demonstrated a decrease in proportions of omission and description errors on trained items immediately posttreatment. Conclusions: Along with generalized improved whole-word naming accuracy, results of the error analysis suggest that a global (i.e., both lexical-semantic and phonological) change in lexical knowledge underlies the observed changes in confrontation naming accuracy following phonomotor treatment.